Enhanced dielectric property and energy storage density of PVDF-HFP based dielectric composites by incorporation of silver nanoparticles-decorated exfoliated montmorillonite nanoplatelets. (May 2018) - Wang, Huan; Xie, Haian; Wang, Shan; Gao, Zhaodongfang; Li, Chuanbin; Hu, Guo-Hua; Xiong, Chuanxi
Abstract: Dielectric constant and breakdown strength are two key factors influencing the energy density of a dielectric material. This paper reports a promising strategy to increase both the dielectric constant and breakdown strength of the PVDF-HFP upon incorporating a low content of silver-deposited exfoliated montmorillonite nanoplatelets (Ag-OMMT). Incorporation of the Ag-OMMT nanoplatelets forms a large number of nanocapacitors, resulting in more interfacial polarization compared to the bare PVDF-HFP under the same applied electric field. Meanwhile, the OMMT nanoplatelets act as the insulating barriers, increasing the breakdown strength of the PVDF-HFP. Consequently, great improvements in the energy storage density are achieved in these dielectric composites. The PVDF-HFP/Ag-OMMT composite film with 4 vol% Ag-OMMT shows an energy density of 10.51 J cm −3 at 400 MV m −1, which is ∼ 2.25 times that of the pure PVDF-HFP film.